Bacterial Infections in Urinary Tract among Pregnant Women in Nassiriyah City, Iraq - Abd Al-Amir , Tamara; Mousa, Hind (University of Thi-Qar Journal of Science, 2023)
Urinary tract infection (UTI) is a very common infection in pregnant women .It causes severe consequences for both the fetus and the mother. This study was accomplished to detect the prevalence  of microorganisms causing UTI in pregnant women. One hundred and twenty participants of pregnant women were included in this study. Urine samples were collected from each participant and cultured on blood and MacConkey agars, followed by macro and microscopic identification and biochemical tests. API 20E and API Staph compact systems were used as a confirmatory test. The results showed that the ratio of positive urine culture was 53 (44.2% ) , and the highest positive urine cultures were detected in the second trimester 23/53 (43.3%). Also, gram positive bacteria especially, Staphyiococcus spp bacteria were the most common frequency (60.2 %) in this study. Also, it was found that  Staphylococcus aureus was the most common microorganism isolated from pregnant  women with UTIs followed by Escherichia coli (19%) . UTI stills a major health problem among pregnant women especially during the last two trimesters of pregnancy. And Staphylococcus aureus is the most dominant pathogen nowadays causing UTIs in different trimesters.